MUHAMMADIYAH EDUCATION'S READINESS IN THE SOCIETY 5.0 ERA - Rahmad Sugianto; Rani Darmayanti; M. Nurul Humaidi (Al'Adalah, 2022)
This study examines Muhammadiyah's readiness in education for the challenges of the society 5.0 era. Technology, Information, and Communication Technologies (ICT) are growing with the urgency of society 5.0 in education based on technology. It is significant to the modern education of Muhammadiyah, which has a progressive education spirit. The method used in this study is a literature review of various references to analyze the relevant data. As a result of the study, Muhammadiyah tried to develop a prophetic civilization, and the concepts of khaira ummah and baldah thayyibah as the recognition and expectations of the people and the nation toward Muhammadiyah, Muhammadiyah intellectuals synergized the potential resources in education. They strengthened religious-social movements as a driving force for the struggle by the spirit inherited by KH Ahmad Dahlan. In this spirit, Muhammadiyah intellectuals challenge and construe society 5.0 based on human-centered. Muhammadiyah education in this era tries to improve educational facilities for digital-based learning in Muhammadiyah schools or madrasas; able to improve teacher human resources to innovate in digital-based learning both online and offline; able to apply humanist learning with the main characteristics of respecting the opinions of others, respecting, and communicating correctly.